Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the [tex]\( x \)[/tex]-coordinate of the solution for the given system of equations
[tex]\[ \left\{\begin{array}{l} 3x + 3y = 3 \\ y = -\frac{1}{2} x + 2 \end{array}\right. \][/tex]
we will solve this system step-by-step.
### Step 1: Simplify the first equation
First, let's simplify the first equation by dividing every term by 3:
[tex]\[ 3x + 3y = 3 \quad \Rightarrow \quad x + y = 1 \][/tex]
This simplification makes the system:
[tex]\[ \left\{\begin{array}{l} x + y = 1 \\ y = -\frac{1}{2}x + 2 \end{array}\right. \][/tex]
### Step 2: Use substitution
We will use substitution to solve for [tex]\( x \)[/tex] and [tex]\( y \)[/tex]. Since we already have [tex]\( y \)[/tex] expressed in terms of [tex]\( x \)[/tex] from the second equation:
[tex]\[ y = -\frac{1}{2}x + 2 \][/tex]
we can substitute this into the first equation:
[tex]\[ x + \left( -\frac{1}{2}x + 2 \right) = 1 \][/tex]
### Step 3: Solve for [tex]\( x \)[/tex]
Now, let's solve for [tex]\( x \)[/tex]:
[tex]\[ x - \frac{1}{2}x + 2 = 1 \][/tex]
[tex]\[ \frac{1}{2}x + 2 = 1 \][/tex]
Subtract 2 from both sides:
[tex]\[ \frac{1}{2}x = -1 \][/tex]
Multiply both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = -2 \][/tex]
### Step 4: Solve for [tex]\( y \)[/tex]
Now that we have [tex]\( x = -2 \)[/tex], substitute this back into the second equation to find [tex]\( y \)[/tex]:
[tex]\[ y = -\frac{1}{2}(-2) + 2 \][/tex]
[tex]\[ y = 1 + 2 \][/tex]
[tex]\[ y = 3 \][/tex]
### Step 5: Verify the solution
Let's verify that [tex]\((x, y) = (-2, 3)\)[/tex] satisfies both original equations:
1. For the first equation [tex]\( 3x + 3y = 3 \)[/tex]:
[tex]\[ 3(-2) + 3(3) = -6 + 9 = 3 \][/tex]
This is correct.
2. For the second equation [tex]\( y = -\frac{1}{2}x + 2 \)[/tex]:
[tex]\[ 3 = -\frac{1}{2}(-2) + 2 = 1 + 2 = 3 \][/tex]
This is also correct.
Thus, the solution to the system of equations is [tex]\((x, y) = (-2, 3)\)[/tex].
### Answer
The [tex]\( x \)[/tex]-coordinate of the solution is [tex]\( \boxed{-2} \)[/tex].
[tex]\[ \left\{\begin{array}{l} 3x + 3y = 3 \\ y = -\frac{1}{2} x + 2 \end{array}\right. \][/tex]
we will solve this system step-by-step.
### Step 1: Simplify the first equation
First, let's simplify the first equation by dividing every term by 3:
[tex]\[ 3x + 3y = 3 \quad \Rightarrow \quad x + y = 1 \][/tex]
This simplification makes the system:
[tex]\[ \left\{\begin{array}{l} x + y = 1 \\ y = -\frac{1}{2}x + 2 \end{array}\right. \][/tex]
### Step 2: Use substitution
We will use substitution to solve for [tex]\( x \)[/tex] and [tex]\( y \)[/tex]. Since we already have [tex]\( y \)[/tex] expressed in terms of [tex]\( x \)[/tex] from the second equation:
[tex]\[ y = -\frac{1}{2}x + 2 \][/tex]
we can substitute this into the first equation:
[tex]\[ x + \left( -\frac{1}{2}x + 2 \right) = 1 \][/tex]
### Step 3: Solve for [tex]\( x \)[/tex]
Now, let's solve for [tex]\( x \)[/tex]:
[tex]\[ x - \frac{1}{2}x + 2 = 1 \][/tex]
[tex]\[ \frac{1}{2}x + 2 = 1 \][/tex]
Subtract 2 from both sides:
[tex]\[ \frac{1}{2}x = -1 \][/tex]
Multiply both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = -2 \][/tex]
### Step 4: Solve for [tex]\( y \)[/tex]
Now that we have [tex]\( x = -2 \)[/tex], substitute this back into the second equation to find [tex]\( y \)[/tex]:
[tex]\[ y = -\frac{1}{2}(-2) + 2 \][/tex]
[tex]\[ y = 1 + 2 \][/tex]
[tex]\[ y = 3 \][/tex]
### Step 5: Verify the solution
Let's verify that [tex]\((x, y) = (-2, 3)\)[/tex] satisfies both original equations:
1. For the first equation [tex]\( 3x + 3y = 3 \)[/tex]:
[tex]\[ 3(-2) + 3(3) = -6 + 9 = 3 \][/tex]
This is correct.
2. For the second equation [tex]\( y = -\frac{1}{2}x + 2 \)[/tex]:
[tex]\[ 3 = -\frac{1}{2}(-2) + 2 = 1 + 2 = 3 \][/tex]
This is also correct.
Thus, the solution to the system of equations is [tex]\((x, y) = (-2, 3)\)[/tex].
### Answer
The [tex]\( x \)[/tex]-coordinate of the solution is [tex]\( \boxed{-2} \)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.